The Effect of Environmental Performance and Governance Performance on the Cost of Debt Mediated by Tax Avoidance - Tiara Fibrianti Ning Tyas; Rida Perwita Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the effect of environmental and governance performance on the cost of debt, with tax avoidance as a mediating variable. This study is motivated by the concern about the sustainability aspect of companies, which is now increasingly crucial in credit risk assessment by creditors. The population of this study is basic materials sector companies listed on the Indonesia Stock Exchange during the period 2020–2023. This study uses a quantitative method with purposive sampling, a sample size of 12 companies, and 4 years of observation. Data were collected from annual financial and sustainability reports and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study indicate that environmental performance and tax avoidance affect the cost of debt, governance performance affects tax avoidance, environmental performance does not affect tax avoidance, governance performance does not affect the cost of debt, tax avoidance does not mediate the relationship between environmental performance and governance performance on the cost of debt. The study contributes both theoretically, by clarifying the limits of tax avoidance as a mediator, and practically, by offering insights for creditors and managers evaluating financing risks.